2022
DOI: 10.3390/biomedicines10071581
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab Use among Patients Who Developed Pulmonary Embolism in the Course of Cytokine Release Storm and COVID-19 Pneumonia—A Retrospective Study

Abstract: Introduction: Thromboembolic events, including mainly pulmonary embolisms and ischemic strokes, occur in up to one-third of COVID-19 patients. As efficacy of tocilizumab (TCZ) among patients with acute pulmonary embolism (PE) was not previously investigated, this study aimed to provide such data. Objectives: The aim of the study was to investigate the effect of TCZ on mortality in patients with confirmed acute pulmonary embolism, cytokine release storm and COVID-19 pneumonia. Patients and methods: Longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…7 , 8 Studies have also shown that mortality may be affected by the initiation of disease-modifying drugs, such as tocilizumab and baricitinib. 9 , 10 Patients with immune deficiency have a significantly higher risk of a severe course of COVID-19 and, according to numerous observations, may have active replication of SARS-CoV-2 for prolonged periods. For this reason, direct antiviral therapy is important for immunodeficient individuals.…”
Section: Introductionmentioning
confidence: 99%
“…7 , 8 Studies have also shown that mortality may be affected by the initiation of disease-modifying drugs, such as tocilizumab and baricitinib. 9 , 10 Patients with immune deficiency have a significantly higher risk of a severe course of COVID-19 and, according to numerous observations, may have active replication of SARS-CoV-2 for prolonged periods. For this reason, direct antiviral therapy is important for immunodeficient individuals.…”
Section: Introductionmentioning
confidence: 99%